Knowledge, Attitude on Health Practices of University Students and Staffs During the COVID-19 Pandemic in Malaysia - Zeti Azreen Ahmad; Kamaruzzaman Abdul Manan (The Journal of Society and Media, 2020)
A novel coronavirus; COVID-19 is posing a great threat to mankind worldwide. The World Health Organization (WHO) has declared the deadly pathogen as a pandemic in view of its alarming spread. Literature affirms that universities have a higher potential to be centres of a pandemic outbreak. The infectious disease could easily transmit from one person to many others within a university vicinity, thus creating a cluster if not properly contained. The Malaysian government has imposed the movement control order (MCO) to flatten the curve of infection. All economic sectors were closed during the MCO period. This study was conducted to explore the knowledge, attitude and health practices towards COVID-19 among internal stakeholders of a public university in Malaysia. An online survey was carried out on the first week of MCO. A total of 340 respondentsD comprised of students and staffs took part in the survey. The regression analysis found knowledge and attitude were significant predictors for adopting appropriate health practices among the internal stakeholders during the new coronavirus outbreak. This present study extends the existing literature on health crisis focusing on internal stakeholders of an institute of higher learning particularly during an early phase of MCO in Malaysia.